A case of sporotrichosis in patient visiting microbiology laboratory in BPKIHS - Gyawali, N; Amatya, R; Shrestha, S; Kumar, A; Agrawal, S; Khanal, B (Sunsari Technical College Journal, 2013)
Sporothrix schenckii is a fungus known to cause infection of skin in the subcutaneous tissues. It is a dimorphic fungus found as hyphae with conidia (2 to 3ìm in diameter) at 25°C, and in cigar-shaped yeast form (4 to 6ìm in diameter) in animal tissues at 37°C. It is ubiquitous in nature and often found in rotting wood, dead plant materials, surface water, and occasionally, swimming pools. Human and animals almost always become infected through a cutaneous lesion. DOI: http://dx.doi.org/10.3126/stcj.v1i1.8661 Sunsari Technical College Journal Vol.1(1) 2012 55-56